A numerical investigation exploring the potential role of porous fencing in reducing firebrand impingement on homes - Atwood, Loren; Wagenbrenner, Natalie (Frontiers in Mechanical Engineering, 2022)
Firebrand impingement is the leading cause of home ignitions from wildland fire. Recently, the use of porous fencing has been proposed as a potential method for mitigating firebrand impingement on homes. A porous fence can act as wind break to alter the near-surface flow and induce particle deposition, as demonstrated in other applications, such as the use of snow fences for protecting roadways from drifting snow. Conservation advocates have proposed the use of fire-resistant vegetation to act as a fence upwind of homes or subdivisions. Porous fences could also be constructed from fire-resistant materials, such as metal, rock, or composites. This work provides a numerical investigation of the effectiveness of porous fencing to reduce firebrand impingement on homes. We conducted a series of numerical experiments to explore the effect of porous fencing on the near-surface flow field and firebrand transport downwind of the fence. Sensitivity of results to various fence, flow, and firebrand properties, including fence height, fence porosity, wind speed, firebrand source location, and firebrand size are investigated. To our knowledge, this is the first study to investigate the concept of using a fence to induce firebrand deposition upwind of homes. Results show that porous fencing can reduce firebrand impingement on homes by up to 35% under certain conditions; however, fencing can also increase impingement on homes. Mitigation effectiveness depends on the proximity of the firebrand source, distance between the fence and home as a function of fence height, wind speed, and firebrand size. A series of key findings and recommendations are provided.